Additive benefits of external focus and enhanced performance expectancy for motor learning - Pascua, L. A. M.; Wulf, G.; Lewthwaite, R. (Journal of Sports Sciences, 2015)
The authors examined the individual and combined influences of 2 factors that have been shown to benefit motor learning: an external focus of attention and enhanced performance expectancies. Another purpose of this study was to gain further insight into the mechanisms underlying these variables. In a factorial design, participants learning a novel motor skill (i.e., throwing with the non-dominant arm) were or were not given external focus instructions, and were or were not provided bogus positive social-comparative feedback to enhance their expectancies. This resulted in 4 groups: external focus, enhanced expectancy, external focus/enhanced expectancy and control. External focus instructions and enhanced expectancies had additive benefits for learning: the external focus/enhanced expectancy group demonstrated the greatest throwing accuracy on both retention and transfer tests, while the accuracy scores of the external focus and enhanced expectancy groups were lower, but higher than those of the control group. Furthermore, self-efficacy was increased by both external focus and enhanced expectancy, and predicted retention and transfer performance. Positive affect was heightened in the enhanced expectancy and external focus/enhanced expectancy groups after practice and predicted transfer performance. The findings suggest that the learning benefits of an external focus and enhanced expectancies mediate learning through partially different mechanisms.